Effect of Acacia mearnsii mulch on soil moisture and temperature, productivity of Zea mays, and certain social aspects - Ochieng, Dorothy A (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScBosb) -- University of Stellenbosch, 1999.